PENERAPAN TEKNIK SCANNING UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN PADA SISWA KELAS IV SD NEGERI 35 KOTA TERNATE - Suhardi Abdullah; Kodrat Hi Karim (Universitas Khairun, 2022)
The objective of this research were to incerased students in reading comprehension at the 4th grade concluded that (1) highly speed reading without ignoring the students understanding, to gained the fact information, special fact and conclusion (2) the percentage of reading comprehension technique scanning in each cycles level of learning activity became high. The result of each cycle by the implementation scanning technique to improve speed reading showed at the first cycle was 4 (47,94%) students were achieved the KKM of 17 students, while the second cycle the students learning activities achieved 14 (76,95 %) of completeness of the students result. Based on the result of the implementation scanning technic using in speed reading concluded that this technic could be used as a strategy and technique in achieved the students reading competence and students developing skills in learning a language skill at SD Negeri 35 Kota Ternate and could be threaten in another elementary school level.